2010
DOI: 10.1017/s1751731109991170
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic parameters of age at first mating, litter size and animal size in Finnish mink

Abstract: Mink skin size in Finland, as well as in other countries, has increased considerably during last decade. However, there are signs that selection for large body size has a negative impact on litter size (LS) and also for survival of kits. Therefore, it is important to study the genetic relationships among fertility traits and animal size (AS). The variance components for age at first mating (AFM) and first three parity LS and AS were estimated using multi-trait restricted maximum likelihood animal model. Data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 15 publications
7
20
0
Order By: Relevance
“…Heritability estimate of LS was 0.11. In other studies heritability for LS in mink has varied from 0.02 to 0.20 (Berg, 1993;Lagerkvist et al, 1994;Rozempolska-Ruciń sca, 2004;Koivula et al, 2009bKoivula et al, , 2010. Thus, the obtained heritability estimate in this study is within the range reported for mink.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Heritability estimate of LS was 0.11. In other studies heritability for LS in mink has varied from 0.02 to 0.20 (Berg, 1993;Lagerkvist et al, 1994;Rozempolska-Ruciń sca, 2004;Koivula et al, 2009bKoivula et al, , 2010. Thus, the obtained heritability estimate in this study is within the range reported for mink.…”
Section: Resultssupporting
confidence: 81%
“…One reason is a strong negative genetic correlation between large animal size (AS) and LS. For example in minks this correlation has varied from (0.18 to (0.28, (Lagerkvist et al, 1994;Rozempolska-Ruciń sca, 2004;Peura et al, 2007;Koivula et al, 2009bKoivula et al, , 2010, and in blue foxes negative correlation has been even higher ((0.36 to (0.43) (Peura et al, 2007;Koivula et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koivula et al. (, ) determined estimated heritability of animal size in October at h 2 = 0.18 (Koivula et al., ) and 0.19 (Koivula et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…The mean weight of wild males is 1,183 g in summer and 1,282 g in winter while both summer and winter mean weight of females is 627 g (Skirnisson et al 2004), which is within the weight range of mink in their native habitats in North America (Dunstone 1993). In comparison, farmed mink body size has increased considerably during the last few decades (Koivula et al 2010) and is now at least double that of feral mink in Iceland (Hanninen et al 2008).…”
Section: Communicated By C Gortázarmentioning
confidence: 98%